Strategi Mitigasi Bencana Pesisir pada Kawasan Wisata Pantai di Desa Korleko Selatan: Analisis Potensi Bahaya dan Upaya Perlindungan Wisatawan - Made Sutha Yadnya; Haeki Manzis; Nanda Febriyani Putri; Miranti Wulan Saputri; Roro Ranti Dea Alfathya; Risna Putri Zahara; Nur Ariza Kurnia Dewi; Lalu Diandra Surya Wardhana; Dwi Lestari; Baiq Faridha Aulya Maharani; Elsya Mayori; Nabilah Putri Nursuha (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
This study analyzes coastal hazards and disaster mitigation strategies in the coastal tourism area of Korleko Selatan Village, East Lombok Regency, West Nusa Tenggara. The main threats identified are coastal abrasion caused by high waves, longshore currents, and oceanographic dynamics, as well as the risk of drowning accidents due to the lack of safety facilities. The research employed a qualitative approach by analyzing satellite imagery, maritime weather forecasts, and literature reviews. Findings indicate that coastal abrasion in Korleko Selatan reaches 1–3 meters annually, worsened by extreme wave conditions of 2.5–4.0 meters during the southeast monsoon period. Additionally, low tourist awareness and limited regulations exacerbate marine accident risks. The proposed mitigation strategies include structural measures (seawalls, breakwaters, mangrove and coral reef rehabilitation) and non-structural measures (risk-based spatial planning, early warning systems, tourist education, evacuation drills, and strengthening local institutions). Integrating disaster mitigation into village development policies and fostering multi-sector collaboration are considered essential to reduce vulnerability and enhance the resilience of coastal communities against increasing disaster threats.